Peran Penguasaan Bahasa Indonesia dalam Mendukung Pembangunan Sosial Ekonomi Nasional: Penelitian - Adel Syesaria A.D; Kevin Daniel Sirait; Selpiana; Ledi Marina Purba (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Indonesian plays a vital role as the nation's unifying language and official means of communication. This study aims to examine the role of Indonesian language proficiency in supporting social and economic development, particularly in education, community participation, and national competitiveness. The method used is qualitative through literature study, document review, interviews, and observation. The results show that Indonesian language proficiency directly impacts the quality of education because it supports the learning process and produces superior human resources. Indonesian also strengthens social cohesion, increases community participation, and opens wider access to employment. In the economic sector, good language skills improve workforce competence and the effectiveness of business communication between regions. However, challenges remain, such as disparities in the quality of language education, low interest among the younger generation, and the influence of foreign languages. Therefore, improving Indonesian language proficiency needs to be a national strategic agenda to strengthen national identity, expand access to development, and enhance global competitiveness.